Peningkatan Kemampuan Siswa-Siswi SMK Negeri 1 Minas Dalam Speech Contest - Edward; Sorta Hutahaean (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2023)
This article is entitiled, “The Improvement of Student’s Ability in Speech Delivery Contest. The research was aimed at improving the ability of the students of State Vocational School I of Minas in delivering speech. After doing the treatment it was found that students were knowledgeable in identifying indicators of .speech contest and in doing exposures towards the factors of speaking in giving a speech, such as appearance/ performance, intonation, fluency, organization including time management/ accuracy, pronunciation and articulation. The result, therefore, in terms of the speaking abilitiy of the students in delivering a speech was gradualy increasing.